Encyclopedia of physical science and technology - Meyers, Robert A. 1936- (Academic Press, 2002)
Nine years has passed since the 1992 second edition of the encyclopedia was published. This completely revised third edition, which is a university and professional level compendium of chemistry, molecular biology, mathematics, and engineering, is refreshed with numerous articles about current research in these fields. For example, the new edition has an increased emphasis on information processing and biotechnology, reflecting the rapid growth of these areas. The continuing Editor-in-Chief, Robert Meyers, and the Board prepared a new topical outline of physical science and technology to define complete coverage. Section editors are either Nobel Laureates or editors of key journals in their fields. Additional Board members representing the global scientific community were also recruited. The new 18-volume edition of the Encyclopedia of Physical Science and Technology, 3E, will have the added feature of an Index Volume, containing abstracts of all of the articles in the encyclopedia. The latest edition of the Encyclopedia of Physical Science and Technology: Has been completely updated with no less than 90% revised material and 50% new content throughout the volumes Presents eighteen volumes, nearly 800 authoritative articles and 14,500 pages Is lavishly illustrated with over 7,000 photographs, illustrations and tables Presents an increased emphasis on the hottest topics such as information processing, environmental science, biotechnology and biomedicine Includes a final Index Volume containing Thematic, Relational and Subject indexes.
Vol. [18]: Reference.
Keywords: fyzika; aplikovaná fyzika; technika; physics; applied physics; technology; encyklopedie; elektronické knihy; encyclopedias; electronic books